PEMANFAATAN AMPAS TAHU DAN LIMBAH JAMUR DALAM PEMBUATAN KOMPOS ORGANIK UNTUK MEMENUHI UNSUR NITROGEN (N) - Farhana, Dita (Bioscientist : Jurnal Ilmiah Biologi, 2013)
One of the most important element for plant growth is nitrogen. Nitrogen is part of the protein, an important constituent part of protoplasm, an enzyme, a biological catalyst agent that speeds up the process of life. Nitrogen is also present as part of the nucleoproteins, amino acids, amines, sugars, polypeptides and organic compounds in plants. The purpose of this study is to know whether the utilization of tofu pulp in the manufacture of organic compost of fungi waste to meet the element of nitrogen (N). The method used in this research is quantitative and qualitative. This type of research is experimental research, which is a systematic, logical, and meticulous type of research in controlling the existing conditions. Analysis of data used, that is calculation manually. The results of this study indicate that the compost control with compost treatment of nitrogen analysis is not much different, the compost control has result among others 1.29%, 1.64%, and 1.74% and the highest is the bottom sample. While the composition of the 10:50 treatment resulted between 1.13%, 0.92%, and 0.98% with the highest yield was in the upper sample, the 30: 50 treatment composition resulted between 1.09%, 1.24%, and 1.17% with the highest yield in the middle sample, and 50:50 treatment compost having a yield of between 0.74%, 0.72%, and 0.41% with the highest yield being in the middle sample. It can be concluded that there is no effect of tofu waste in making organic compost of mushroom waste, except with the treatment of 30:50.